Spray deposited CuInS2/TiO2 thin film solar cells - Kaliang, J.; Chaisitsak, S. (My University, 2013)
Copper indium sulfide (CIS) solar cells with Ag/CIS/TiO2/FTO/ glass structure were fabricated by non-vacuum methods. The nanoporous TiO 2 and nanocrystalline CIS films were prepared by screen-printing and spray pyrolysis techniques, respectively. The obtained films were examined using field-emission scanning electron microscopy and X-ray diffraction. The solar cell properties were characterized under AM 1.5. The porous nature of TiO 2 layer was found to cause the formation of nanocrystalline CIS with a very small grain size within the TiO2 matrix. The photocurrent could not be observed in any devices without a TiO2 layer (i.e. CIS/FTO), while it was detected for the devices consisting of TiO2 layer (i.e. CIS/TiO2/FTO). The thickness of TiO2 layer was optimized for maximum efficiency. The highest efficiency obtained solar cells was 2.3 × 10-5 % (Voc: 0.147 V, Jsc: 6.5×10-7A/cm2, FF: 0.24) with a 3-μm-thick TiO2. © 2013 IEEE.
Keywords: CuInS2; screen printing; solar cells; spray deposition; TiO2